Correction: Polymer-bound antioxidants in grafted membranes for fuel cells. Issue 4 (12th January 2017) - Buchmüller, Yves; Wokaun, Alexander; Gubler, Lorenz
Abstract : Correction for 'Polymer-bound antioxidants in grafted membranes for fuel cells' by Yves Buchmüller et al., J. Mater. Chem. A, 2014, 2, 5870–5882.